2020
DOI: 10.1177/0022429420974389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tonic Drone Accompaniments on the Intonation of Collegiate Wind Instrumentalists

Abstract: The purpose of this study was to examine the effects of tonic drone accompaniments on the intonation of collegiate wind instrumentalists. Participants ( N = 68) played an excerpt of the melody “Long, Long Ago” in three conditions: a mono drone (tonic note only), dyad drone (tonic plus fifth), and a control condition (no drone). Results indicated no significant effects on intonation performance due to drone condition. However, participants’ ratings of their own intonation accuracy differed significantly based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…According to results of some prior research, there is disagreement about the way audio materials help in the development of intonation. Some studies consider this material useless for developing intonation (Laux, 2015;Springer et al, 2021;Zabanal, 2019Zabanal, , 2020a. Others concluded it can have other valuable benefits, for example, gaining pitch performance accuracy, but when used alongside other kinds of exercises not only as accompaniment but also for other intonation practice (e.g., singing) (Smith, 1995).…”
Section: Synthesis Of Results: a Pedagogical Proposalmentioning
confidence: 99%
See 2 more Smart Citations
“…According to results of some prior research, there is disagreement about the way audio materials help in the development of intonation. Some studies consider this material useless for developing intonation (Laux, 2015;Springer et al, 2021;Zabanal, 2019Zabanal, , 2020a. Others concluded it can have other valuable benefits, for example, gaining pitch performance accuracy, but when used alongside other kinds of exercises not only as accompaniment but also for other intonation practice (e.g., singing) (Smith, 1995).…”
Section: Synthesis Of Results: a Pedagogical Proposalmentioning
confidence: 99%
“…The results of a similar study (accompaniment in charge of the E4 sound only) involving more experienced students (2-11 years) support these negative results (Zabanal, 2019). In a recent examination of college wind instrumentalists’ intonation (Springer et al, 2021), a single group of students (repeated measures) played a familiar melody with three types of accompaniment: (a) a single C3 sound, (b) a harmonic interval: C3-G3, and (c) no accompaniment. Results revealed that the use of accompaniments had no effect on intonation accuracy.…”
Section: Learning Intonation On Violin and Violamentioning
confidence: 99%
See 1 more Smart Citation
“…Otras investigaciones sugieren a los instrumentistas de viento utilizar un acompañamiento armónico durante su ejercitación (un bordón o 'drone') (Puangsamlee y Fyr, 2018) o bien una 'nota pedal' (un sonido continuo, generalmente la nota tónica) (Springer et al, 2020). Sin embargo, el estudio de Zabanal (2019) no confirma resultados positivos del uso de drones, aunque se trata de un trabajo limitado y de tipo exploratorio.…”
Section: La Enseñanza De La Entonación En Instrumentos De Viento-metalunclassified
“…Las actividades relacionadas con la entonación consisten en tocar e igualar sonidos largos del profesor, tocar intervalos determinados para conseguir la entonación correcta, tocar escalas y arpegios, tocar con acompañamiento de una "nota-pedal" (sonido largo o mantenido), de un bordón (un intervalo armónico) o de un ostinato (patrón repetido de sonidos). Estas actividades están en línea con estudios que recomiendan este tipo de actividades y estrategias (Springer et al, 2020), aunque existe controversia respecto a la efectividad de los bordones (por ejemplo, Zabanal, 2019).…”
Section: Contenidos De Entonaciónunclassified